A self-audit tool for threat scanning discovery and feedback - Lim, Bryan Kian Hock (2019)
With cyber-attacks such as credential stuffing and password spraying amongst other attacks that take advantages of vulnerabilities present in web applications on the rise, there is a strong and increasing emphasis on consistent and timely audits done to web applications, infrastructures and passwords to detect and prevent such attacks. In order to combat and prevent such cyber-attacks, a self-audit tool for threat scanning discovery and feedback is developed to allow users to conduct audits on web applications and passwords. With a tool that integrates both password auditing and web application scanning, it increases the efficiency of the auditors as they do not have to use multiple tools to conduct the audit. In this report, the architecture, development and implementation of the self-audit tool for threat scanning discovery and feedback is explained.